MANAJEMEN KEUANGAN PENDIDIKAN MASA PANDEMI COVID-19 DI MTs HARAPAN BARU CIAMIS - hendriana, hendriana; kusmawan, dedi; nurhayati, elin (Journal of Management Review, 2025)
Education plays an important role in improving the quality of human resources, and financial management of education is one of the most strategic activities for the sustainability of education. This study aims to describe how education financial management starts from planning, implementation, to financial supervision during the Covid-19 pandemic which is certainly very interested in research. The approach in this study uses a qualitative research approach with a case study method. Data collection techniques using triangulation methods, namely, interviews, observation, and documentation. The place for our research is at MTs Harapan Baru Ciamis. The subjects in the study were principals, committees, school treasurers, and teachers. Based on the findings, during the COVID-19 pandemic, the focus of financing was on purchasing medical equipment, developing libraries, and honoring teachers. The impact of the Covid 19 pandemic on MTs Harapan Baru Ciamis is very clear, the use of the budget is adjusted to the need to deal with the covid-19 outbreak. In terms of reporting or the use of BOS funds, according to the head of MTs Harapan Baru Ciamis, during the Covid 19 pandemic, getting leeway is not the same as normal.